pellet

JP7638678B2Active Publication Date: 2025-03-04MITSUI CHEMICALS INC
View PDF 23 Cites 0 Cited by

Patent Information

Application Number
JP2020194488
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-24
Publication Date
2025-03-04
Estimated Expiration
2040-11-24

Smart Images

  • Figure 0007638678000003
    Figure 0007638678000003
  • Figure 0007638678000001
    Figure 0007638678000001
  • Figure 0007638678000002
    Figure 0007638678000002
Patent Text Reader

Abstract

SOLUTION: A pellet containing an ethylene-1-octene copolymer satisfies the following requirements (i)-(iii). (i) It contains an ethylene-induced constitutional unit (a) of 51-99 mol% and a 1-octene-induced constitutional unit (b) of 1-49 mol% (where the total of the constitutional unit (a) and constitutional unit (b) is 100 mol%). (ii) It has, in accordance with ASTM D 1238, a melt flow rate (MFR) of 0.5-20 g / 10 min. at 190°C and 2.16 kg load. (iii) It has a density of 850-870 kg / m3.EFFECT: The inventive pellet of an ethylene-1-octene copolymer has excellent blocking resistance while holding high impact resistance and high flowability.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to pellets, and more particularly to pellets containing an ethylene-1-octene copolymer, which have excellent blocking resistance. [Background technology]

[0002] Various resin compositions have been developed for various applications. As described later, ethylene-1-octene copolymers are used for some applications, but further improvements are required for the properties required for each application.

[0003] Patent Document 1 discloses a composition containing an ethylene-1-octene copolymer and describes that it has excellent low-temperature impact performance. Patent Document 2 discloses an ethylene-1-octene copolymer produced using a metallocene catalyst.

[0004] For example, when ethylene-1-octene copolymers are used in automobile applications, high impact resistance and high fluidity have been required. To meet this requirement, a method of decreasing the density of the ethylene-1-octene copolymer and increasing its fluidity has been adopted. However, since the ethylene-1-octene copolymers with decreased density and increased fluidity contain many components that crystallize even at low temperatures, when pellets of the copolymer are filled into packaging bags, flexible container bags, etc. and transported by truck or ship, or stored in a warehouse for a long period of time during the summer, blocking due to compaction occurs, and the pellets may not be usable for molding. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 8-501343 [Patent Document 2] Special Publication No. 2014-517012 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide pellets containing an ethylene-1-octene copolymer that have excellent blocking resistance while maintaining high impact resistance and high fluidity. [Means for solving the problem]

[0007] The present invention relates to, for example, the following [1] to [4]. [1] Pellets containing an ethylene-1-octene copolymer that satisfies the following requirements (i) to (iii): (i) The content of structural units (a) derived from ethylene is 51 to 99 mol %, and the content of structural units (b) derived from 1-octene is 1 to 49 mol % (the total of structural units (a) and structural units (b) is 100 mol %). (ii) The melt flow rate (MFR) at 190°C under a load of 2.16 kg according to ASTM D 1238 is 0.5 to 20 g / 10 min. (iii) Density is 850-870 kg / m 3 It is.

[0008] [2] The pellet according to [1], which is produced by an extruder, characterized in that the longest length (L) of the pellet in the extrusion direction of the extruder is 1.5 to 5.0 mm, and the longest length (D) of the pellet in the direction perpendicular to the extrusion direction is 3.5 to 6.0 mm. [3] The pellet according to [1] or [2], characterized in that the half-width of the peak of the composition distribution obtained by crystallization elution fractionation chromatography (CEF) is 25°C or less.

[0009] [4] A pellet according to any one of [1] to [3], characterized in that the melting point [Tm] (°C) and the content [C8 content] (mol%) of the structural unit (b) derived from 1-octene satisfy the following relationship (1): [Tm]<-6.081×[C8 content]+144 (1) Effect of the Invention

[0010] The pellets of the present invention contain an ethylene-1-octene copolymer and have excellent blocking resistance while retaining high impact resistance and high fluidity. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is an explanatory diagram showing the maximum length (L) of the pellets in the extrusion direction of the extruder and the maximum length (D) of the pellets in a direction perpendicular to the extrusion direction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The pellets of the present invention contain an ethylene-1-octene copolymer that satisfies the following requirements (i) to (iii). (i) The content of structural units (a) derived from ethylene is 51 to 99 mol %, and the content of structural units (b) derived from 1-octene is 1 to 49 mol % (the total of structural units (a) and structural units (b) is 100 mol %).

[0013] In the ethylene-1-octene copolymer, the lower limit of the range of the content of the structural unit (a) derived from ethylene is preferably 60 mol%, more preferably 70 mol%, even more preferably 75 mol%, and particularly preferably 80 mol%. The upper limit of the range of the content of the structural unit (a) derived from ethylene is preferably 97 mol%, more preferably 94 mol%, even more preferably 90 mol%, and particularly preferably 86 mol%. The lower limit of the range of the content of the structural unit (b) derived from 1-octene is preferably 3 mol%, more preferably 6 mol%, even more preferably 10 mol%, and particularly preferably 14 mol%. The upper limit of the range of the content of the structural unit (b) derived from 1-octene is preferably 40 mol%, more preferably 30 mol%, even more preferably 25 mol%, and particularly preferably 20 mol%.

[0014] When the content of the structural unit (a) and the structural unit (b) in the ethylene-1-octene copolymer is within the above range, the copolymer exhibits excellent and well-balanced mechanical strength and impact resistance. (ii) The melt flow rate (MFR) at 190°C under a load of 2.16 kg according to ASTM D 1238 is 0.5 to 20 g / 10 min.

[0015] In the ethylene / 1-octene copolymer, the lower limit of the melt flow rate range is preferably 0.8 g / 10 min, more preferably 1.2 g / 10 min, even more preferably 1.5 g / 10 min, and particularly preferably 1.7 g / 10 min. The upper limit of the melt flow rate range is preferably 19.5 g / 10 min, more preferably 19.0 g / 10 min, even more preferably 18.5 g / 10 min, and particularly preferably 18.0 g / 10 min. An ethylene / 1-octene copolymer having a melt flow rate within the above range has high fluidity and is advantageous in producing good pellets, molded bodies, and automotive interior and exterior materials during molding processing. (iii) Density is 850 to 870 kg / m 3 It is.

[0016] In the ethylene-1-octene copolymer, the lower limit of the density range is preferably 851 kg / m 3 , more preferably 852 kg / m 3 , more preferably 853 kg / m 3 , particularly preferably 854 kg / m 3 The upper limit of the density range is preferably 866 kg / m 3 min, more preferably 864 kg / m 3 , more preferably 863 kg / m 3 , particularly preferably 862 kg / m 3 Ethylene-1-octene copolymers having a density within the above range are advantageous in producing impact-resistant and lightweight molded articles.

[0017] The ethylene-1-octene copolymer preferably has a half-width of a peak in a composition distribution obtained by crystallization elution fractional chromatography (CEF) of 25° C. or less. The half width of the peak of the composition distribution is more preferably 24°C or less, even more preferably 23°C or less, even more preferably 22°C or less, and particularly preferably 21°C or less. The ethylene-1-octene copolymer having the half width of the peak of the composition distribution in the above range has a small amount of low crystalline components and is less prone to blocking. In addition, the peak temperature of the composition distribution obtained by crystallization elution fractionation chromatography (CEF) is preferably 50°C or less. The peak temperature of the composition distribution is more preferably 40°C or less, even more preferably 30°C or less, even more preferably 28°C or less, and particularly preferably 25°C or less. The ethylene-1-octene copolymer having the peak temperature of the composition distribution in the above range has a small amount of crystalline components, is flexible, and has excellent impact resistance.

[0018] The method for measuring the half-width and peak temperature of the peak of the composition distribution obtained by crystallization elution fractionation chromatography (CEF) will be described in detail in the Examples below. The ethylene-1-octene copolymer preferably has a melting point [Tm] (° C.) and a content [C8 content] (mol %) of the structural unit (b) derived from 1-octene that satisfies the following relationship (1). [Tm]<-6.081×[C8 content]+144 (1)

[0019] When the ethylene-1-octene copolymer satisfies the relational formula (1), the pellets of the present invention have a property of being less prone to blocking even when the density is reduced and the fluidity is increased.

[0020] In order to reduce the low crystal content of ethylene-1-octene copolymers while maintaining low density, it is necessary to narrow the composition distribution of the ethylene-1-octene copolymer. The composition distribution depends on the reactivity ratio of the main monomer ethylene and the comonomer 1-octene, which is determined by the type of catalyst. When the same type of monomer is reactive, the content of the comonomer 1-octene must be increased to reduce density. Increasing the comonomer content broadens the composition distribution and increases the melting point. In other words, ethylene-1-octene copolymers with a wide composition distribution that is prone to blocking tend to have a higher melting point than ethylene-1-octene copolymers with a narrow composition distribution. Therefore, ethylene-1-octene copolymers that satisfy the above formula are less likely to block even when they are made low-density and highly fluid.

[0021] In the ethylene-1-octene copolymer, the ratio (I10 / I2) of the melt flow rate (MFR) at 190°C under a load of 10 kg to the melt flow rate (MFR) at 190°C under a load of 2.16 kg according to ASTM D1238 is preferably 10.0 or less, more preferably 9.0 or less, even more preferably 8.0 or less, still more preferably 7.7 or less, and particularly preferably 7.5 or less. An ethylene-1-octene copolymer having an I10 / I2 in the above range can easily give a molded article having excellent impact resistance.

[0022] The ethylene-1-octene copolymer has a ratio of weight average molecular weight (Mw) to number average molecular weight (Mn) calculated as polypropylene, determined by gel permeation chromatography (GPC) (Mw / Mn, molecular weight distribution) of preferably 4.0 or less, more preferably 3.5 or less, even more preferably 3.0 or less, still more preferably 2.8 or less, and particularly preferably 2.5 or less. The ethylene-1-octene copolymer having a molecular weight distribution in the above range has a well-balanced excellent property of mechanical strength, impact resistance, and low stickiness.

[0023] The ethylene-1-octene copolymer has a melting point (Tm) measured by differential scanning calorimetry (DSC) of preferably 15° C., more preferably 19° C., even more preferably 22° C., still more preferably 25° C., and particularly preferably 28° C. The upper limit of the melting point (Tm) is preferably 80° C., more preferably 60° C., even more preferably 55° C., still more preferably 50° C., and particularly preferably 48° C. Ethylene-1-octene copolymer (B) having a melting point within the above range is excellent in terms of the balance between blocking resistance and impact resistance.

[0024] The ethylene-1-octene copolymer has a heat of fusion (ΔH) determined from a melting peak observed by differential scanning calorimetry (DSC) of preferably 60 J / g or less, more preferably 53 J / g or less, even more preferably 51 J / g or less, still more preferably 49 J / g or less, and particularly preferably 48 J / g or less. The ethylene-1-octene copolymer (B) having a heat of fusion (ΔH) within the above range has excellent impact resistance. The ethylene-1-octene copolymer can be produced by any method without particular limitation, but can be suitably produced by using a metallocene catalyst.

[0025] The pellets of the present invention may further contain, in addition to the ethylene-1-octene copolymer, other polymers and additives other than those mentioned above, as necessary. Examples of the other polymers include homopolypropylene and copolymers of propylene and an α-olefin having 2 to 20 carbon atoms other than propylene. The copolymer may be a random copolymer or a block copolymer. The content of the other polymers in the propylene-based resin composition of the present invention is preferably 0 to 25% by mass, more preferably 0.1 to 20% by mass.

[0026] Examples of additives include, but are not limited to, weather resistance stabilizers, heat resistance stabilizers, ultraviolet absorbers, infrared absorbers, antistatic agents, antislip agents, antiblocking agents, antifogging agents, lubricants, pigments, dyes, plasticizers, antioxidants, hydrochloric acid absorbers, antioxidants, crystal nucleating agents, antifungal agents, antibacterial agents, flame retardants, organic fillers, and softeners. These additives may be used alone or in combination.

[0027] The pellets of the present invention are produced by an extruder, and the maximum length (L) of the pellets in the extrusion direction of the extruder is preferably 1.5 to 5.0 mm, and the maximum length (D) of the pellets in the direction perpendicular to the extrusion direction is preferably 3.5 to 6.0 mm.

[0028] FIG. 1 is a schematic diagram showing one specific example of pellets, with a horizontally long ellipse representing one pellet. In FIG. 1, the longest length (L) of the pellet in the extrusion direction of the extruder is indicated by "L". Furthermore, in FIG. 1, the cross section of the pellet in a direction perpendicular to the extrusion direction of the extruder is conceived, and the cross section having the largest diameter among the cross sections is represented by the curved line and dotted line shown in the ellipse of the pellet. In FIG. 1, the longest length (D) of the pellet in the direction perpendicular to the extrusion direction is indicated by "D".

[0029] The pellets containing the ethylene / 1-octene copolymer have a length (L) of more preferably 1.8 to 4.7 mm, and further preferably 2.0 to 4.5 mm, and a length (D) of more preferably 3.7 to 5.7 mm, and further preferably 4.0 to 5.5 mm. The pellets containing the ethylene / 1-octene copolymer, whose length (L) and length (D) are within the above ranges, have excellent handleability during molding.

[0030] The method for producing the pellets of the present invention is not particularly limited, and for example, a conventionally known production method can be used. A method can be adopted in which the components containing the ethylene-1-octene copolymer are melt-kneaded and then granulated or pulverized. The melt-kneading method is not particularly limited, and a commonly used known mixer such as a kneader, a roll mill, a Banbury mixer, or a single-screw or twin-screw extruder can be used. This method can produce high-quality pellets in which the components and additives are uniformly dispersed and mixed.

[0031] The pellets of the present invention have excellent blocking resistance while retaining high impact resistance and high fluidity. Taking advantage of this characteristic, various molded articles can be produced from the pellets of the present invention.

[0032] The molded article can be produced by molding the pellets of the present invention by a conventionally known molding method, for example, a blow molding method, an injection molding method, a press molding method, an extrusion molding method, an inflation molding method, an extrusion blow molding method, an injection blow molding method, a vacuum molding method, a calendar molding method, or a melt T-die casting method.

[0033] Examples of the molded article include automobile parts such as automobile interior and exterior materials, etc. The automobile interior and exterior materials are not particularly limited, and examples include automobile parts molded by injection molding, etc. Specific examples of automobile interior materials include trim, instrument panels, and column covers, and specific examples of automobile exterior materials include fenders, bumpers, side moldings, mudguards, and mirror covers. EXAMPLES

[0034] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these. Example 1 The ethylene-1-octene copolymer pellets used were obtained by the following production method.

[0035] <Production of ethylene-1-octene copolymer pellets> A hexane solution of triisobutylaluminum as a cocatalyst at 20 mmol / hr and [bis(4-methoxyphenyl)methylene(η 5- Cyclopentadienyl)(η 5- A hexane solution of tetramethyloctahydrodibenzofluorenyl) hafnium dichloride was fed at a rate of 0.0075mmol / hr, and a hexane slurry solution of triphenylcarbenium tetrakis(pentafluorophenyl)borate was fed at a rate of 0.034mmol / hr, and dehydrated and purified normal hexane was continuously fed so that the total amount of the catalyst solution and the dehydrated and purified normal hexane used as the polymerization solvent was 37.3L / hr. At the same time, ethylene was continuously fed at a rate of 6.4kg / hr, 1-octene at 9.0kg / hr, and hydrogen at 110NL / hr to another feed port of the polymerization vessel, and continuous solution polymerization was carried out under the conditions of a polymerization temperature of 130°C, a total pressure of 2.5MPaG, and a residence time of 0.5 hours. The n-hexane / toluene mixed solution of ethylene-1-octene copolymer produced in the polymerization reactor was continuously discharged through an outlet at the bottom of the polymerization reactor. The jacket was heated to 3 kg / cm so that the n-hexane / toluene mixed solution of ethylene-1-octene copolymer was kept at 150°C. 2The mixture was then introduced into a connecting pipe heated by steam. Just before the connecting pipe, a feed port was installed for injecting methanol, a catalyst deactivator, and methanol was injected at a rate of about 11 L / hr to join the normal hexane / toluene mixed solution of ethylene-1-octene copolymer. The normal hexane / toluene mixed solution of ethylene-1-octene copolymer, which was kept at about 200°C in the steam-jacketed connecting pipe, was continuously sent to the flash tank by adjusting the opening of the pressure control valve installed at the end of the connecting pipe so as to maintain about 2.5 MPaG. During the transfer to the flash tank, the solution temperature and the opening of the pressure control valve were set so that the pressure in the flash tank was about 0.05 MPaG and the temperature of the steam part in the flash tank was maintained at about 200°C. The mixture was then passed through a single-screw extruder with a die temperature set to 190°C, the strands were cooled in a water tank, and the strands were cut by a pellet cutter to obtain ethylene-1-octene copolymer as pellets. The yield was 7.9 kg / 2 hr.

[0036] The physical properties of the ethylene-1-octene copolymer obtained above were measured by the methods shown below. The yield and measurement results of the ethylene-1-octene copolymer are shown in Table 1. In addition, the blocking force of the ethylene-1-octene copolymer pellets and the collapse of the pellet aggregates were evaluated by the following methods. The results are shown in Table 2.

[0037] (Comonomer content (composition)) The comonomer content was measured using a JNM GX-400 NMR measuring device manufactured by JEOL Ltd. 0.35 g of sample was dissolved in 2.0 ml of hexachlorobutadiene by heating. After filtering the solution through a glass filter (G2), 0.5 ml of deuterated benzene was added and the solution was placed in an NMR tube with an inner diameter of 10 mm and heated at 120°C. 13 C-NMR measurements were performed. The number of measurements was set to 8000 or more. 13 The ethylene content (mol%) and 1-octene content (mol%) in the copolymer were quantified by C-NMR spectroscopy.

[0038] (density) Density was measured according to ASTM D1505.

[0039] (MFR) The melt flow rate (MFR) was measured in accordance with ASTM D1238 under the conditions of 190°C, 2.16 kg load and 190°C, 10 kg load.

[0040] (Weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn)) The ethylene-1-octene copolymer was subjected to gel permeation chromatography (GPC) measurement, and the polystyrene equivalent molecular weight of each fraction, Mi-PSt, was obtained. Next, Mi-PSt was [η]i-PSt·Mi-PSt=[η]i-EPR·Mi-EPR, [η]i-PSt = 1.37 × 10 -4 Mi-PSt0.686, and [η]i-EPR=7.2×10 -4 Mi-EPR0.667 The molecular weight was converted to an EPR-equivalent molecular weight Mi-EPR using the following formula: The molecular weight distribution (Mw / Mn) was calculated using the EPR-equivalent molecular weight.

[0041] Gel permeation chromatography (GPC) was performed using a Waters gel permeation chromatograph Alliance GPC-2000 model, as follows. The separation columns were two TSKgel GNH6-HT and two TSKgel GNH6-HTL, each with a diameter of 7.5 mm and a length of 300 mm. The column temperature was 140°C, the mobile phase was o-dichlorobenzene (Wako Pure Chemical Industries, Ltd.) and 0.025 wt% BHT (Takeda Pharmaceutical Co., Ltd.) as an antioxidant, and the flow rate was 1.0 ml / min. The sample concentration was 15 mg / 10 ml, the sample injection volume was 500 μl, and a differential refractometer was used as the detector. Standard polystyrene had molecular weights of Mw<1000 and Mw>4×10 6 For the 1000≦Mw≦4×10 6The material used was manufactured by Pressure Chemical Company.

[0042] (Peak temperature and half-width of composition distribution) The peak temperature and half-width of the composition distribution were measured using a high-throughput composition distribution analyzer manufactured by Polymer Char. After conditioning the specimen at 23°C ± 2°C for 72 hours or more in a CEF (crystallization elution fractionation chromatography) measurement device, the specimen was cooled from 95°C to -20°C at a temperature drop rate of 1.0°C / min, and then heated to 140°C at a temperature rise rate of 4.0°C / min. The peak temperature and half-width were determined.

[0043] (Melting point and heat of fusion) After conditioning the specimen in a DSC (differential scanning calorimetry) measuring device at 23°C ± 2°C for 72 hours or more, the specimen was cooled to -40°C, then heated to 200°C at a rate of 10°C / min, held at 200°C for 10 minutes, cooled to -20°C at a rate of 10°C / min, held at -20°C for 1 minute, and then measured again at a rate of 10°C / min to create a DSC curve. The melting point obtained at this time was taken as Tm, and the heat of fusion calculated from the melting peak was taken as ΔH.

[0044] (The maximum length of the pellet (L) and the maximum length of the pellet (D)) Ten pellets were randomly selected, and the longest length of the pellet in the extrusion direction of the extruder (L) and the longest length of the pellet in the direction perpendicular to the extrusion direction (D) were measured with a vernier caliper. The respective average values ​​were taken as the longest length of the pellet (L) (mm) and the longest length of the pellet (D) (mm).

[0045] (Pellet blocking test) Ethylene-1-octene copolymer pellets were packed in a plastic bag so that the size was 90 mm in length, 90 mm in width, and 20 mm in height, and a load was applied so that the pressure on the sample was 1.2 kPa. In this state, the sample was aged at 35°C for one day, and then stored at -10°C for seven days. The pellet aggregate was evaluated for pellet blocking force using a push-pull gauge and the degree of collapse of the pellet aggregate after the test. The degree of collapse of the pellet aggregate after the test was judged visually according to the following criteria.

[0046] A: The pellet aggregate as a whole crumbles easily. B: The pellet aggregate crumbles at the blocking force measurement points and also at other points, but some lumps remain. C: The pellet aggregate collapses only at the blocking force measurement point. D: The pellet aggregate does not crumble.

[0047] Example 2 Pellets of ethylene-1-octene copolymer were produced in the same manner as in Example 1, except that the feed amount of 1-octene, the feed amount of the main catalyst, and the polymerization temperature were adjusted as shown in Table 1. The physical properties of the obtained ethylene / 1-octene copolymer were measured in the same manner as in Example 1. The yield and measurement results of the ethylene / 1-octene copolymer are shown in Table 1. Furthermore, the blocking force of the ethylene-1-octene copolymer pellets and the collapse of the pellet aggregates were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0048] Example 3 Ethylene-1-octene copolymer pellets were produced in the same manner as in Example 1, except that the feed amounts of 1-octene and the main catalyst were adjusted as shown in Table 1. The physical properties of the obtained ethylene / 1-octene copolymer were measured in the same manner as in Example 1. The yield and measurement results of the ethylene / 1-octene copolymer are shown in Table 1. Furthermore, the blocking force of the ethylene-1-octene copolymer pellets and the collapse of the pellet aggregates were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0049] Example 4 Ethylene-1-octene copolymer pellets were produced in the same manner as in Example 1, except that the feed amounts of 1-octene and the main catalyst were adjusted as shown in Table 1. The physical properties of the obtained ethylene / 1-octene copolymer were measured in the same manner as in Example 1. The yield and measurement results of the ethylene / 1-octene copolymer are shown in Table 1. Furthermore, the blocking force of the ethylene-1-octene copolymer pellets and the collapse of the pellet aggregates were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0050] Example 5 Ethylene-1-octene copolymer pellets were produced in the same manner as in Example 1, except that the feed amounts of 1-octene and the main catalyst were adjusted as shown in Table 1. The physical properties of the obtained ethylene / 1-octene copolymer were measured in the same manner as in Example 1. The yield and measurement results of the ethylene / 1-octene copolymer are shown in Table 1. Furthermore, the blocking force of the ethylene-1-octene copolymer pellets and the collapse of the pellet aggregates were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0051] Example 6 Ethylene-1-octene copolymer pellets were produced in the same manner as in Example 1, except that the feed amounts of 1-octene and the main catalyst were adjusted as shown in Table 1. The physical properties of the obtained ethylene / 1-octene copolymer were measured in the same manner as in Example 1. The yield and measurement results of the ethylene / 1-octene copolymer are shown in Table 1. Furthermore, the blocking force of the ethylene-1-octene copolymer pellets and the collapse of the pellet aggregates were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0052] Example 7 Ethylene-1-octene copolymer pellets were produced in the same manner as in Example 1, except that the feed amounts of 1-octene and the main catalyst were adjusted as shown in Table 1. The physical properties of the obtained ethylene / 1-octene copolymer were measured in the same manner as in Example 1. The yield and measurement results of the ethylene / 1-octene copolymer are shown in Table 1. Furthermore, the blocking force of the ethylene-1-octene copolymer pellets and the collapse of the pellet aggregates were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0053] Example 8 Ethylene-1-octene copolymer pellets were produced in the same manner as in Example 1, except that the feed amounts of 1-octene and the main catalyst were adjusted as shown in Table 1. The physical properties of the obtained ethylene / 1-octene copolymer were measured in the same manner as in Example 1. The yield and measurement results of the ethylene / 1-octene copolymer are shown in Table 1. Furthermore, the blocking force of the ethylene-1-octene copolymer pellets and the collapse of the pellet aggregates were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0054] Comparative Example 1 As pellets of ethylene-1-octene copolymer, ENGAGE 8842 (trade name, manufactured by Dow Chemical) was used. Various physical properties of this ethylene-1-octene copolymer were measured in the same manner as in Example 1. The measurement results are shown in Table 1. Furthermore, the blocking force of the ethylene-1-octene copolymer pellets and the collapse of the pellet aggregates were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0056] Furthermore, the blocking force of the ethylene-1-octene copolymer pellets and the collapse of the pellet aggregates were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0057] [Table 1]

[0058] [Table 2]

Claims

1. The following requirements (i) to (iii) are met: The melting point [Tm] (° C.) and the content [C8 content] (mol %) of the structural unit (b) derived from 1-octene satisfy the following relationship (1), [Tm]<-6.081×[C8 content]+144 (1) and, obtained using [bis(4-methoxyphenyl)methylene(η 5 -cyclopentadienyl)(η 5 -tetramethyloctahydrodibenzofluorenyl)]hafnium dichloride as the main catalyst, Pellets containing an ethylene / 1-octene copolymer. (i) The content of structural units (a) derived from ethylene is 51 to 86 mol %, and the content of structural units (b) derived from 1-octene is 14 to 49 mol % (the total of structural units (a) and structural units (b) is 100 mol %). (ii) The melt flow rate (MFR) at 190° C. under a load of 2.16 kg according to ASTM D1238 is 2.0 to 20 g / 10 min. (iii) density is 850 to 862 kg / m 3 It is.

2. The pellet according to claim 1, characterized in that the pellet is produced by an extruder, and the longest length (L) of the pellet in the extrusion direction of the extruder is 1.5 to 5.0 mm, and the longest length (D) of the pellet in a direction perpendicular to the extrusion direction is 3.5 to 6.0 mm.

3. 3. The pellet according to claim 1 or 2, wherein the half-width of the peak of the composition distribution obtained by crystallization elution fractionation chromatography (CEF) is 25° C. or less.

4. A process for producing an ethylene-1-octene copolymer, comprising the steps of: polymerizing ethylene and 1-octene using [bis(4-methoxyphenyl)methylene(η 5 -cyclopentadienyl)(η 5 -tetramethyloctahydrodibenzofluorenyl)]hafnium dichloride as a main catalyst; and The ethylene / 1-octene copolymer, the content of structural units derived from ethylene is 51 to 86 mol % and the content of structural units (b) derived from 1-octene is 14 to 49 mol % (the total of structural units (a) and structural units (b) being 100 mol %); A melt flow rate (MFR) of 2.0 to 20 g / 10 min at 190° C. under a load of 2.16 kg according to ASTM D 1238; The density is 850 to 862 kg / m 3 , The melting point [Tm] (°C) and the content [C8 content] (mol%) of the structural unit (b) derived from 1-octene satisfy the following relationship (1). [Tm]<-6.081×[C8 content]+144 (1) Ethylene / 1-octene copolymer A method for producing pellets comprising the steps of:

Citation Information

Patent Citations

  • Impact modification of thermoplastics

    JP1996501343A

  • Polypropylene resin composition

    JP1998330559A

  • Multilayer film

    JP1999291420A

  • Thermoplastic elastomer composition excellent in abrasion resistance

    JP2000072892A

  • Polyphenylene sulfide resin composition

    JP2000198923A